2005
DOI: 10.1007/bf02849870
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of OROS® methylphenidate compared with atomoxetine in children with ADHD: A multicenter, randomized prospective study

Abstract: This community-based study was designed to evaluate treatment outcomes with OROS methylphenidate (MPH) and atomoxetine in children with attentiondeficit/hyperactivity disorder (ADHD), as assessed by physicians and parents in a setting that resembles clinical practice. In a multicenter, prospective, open-label study, children 6 to 12 years of age with ADHD were randomized (2:1, respectively) to 3 weeks of treatment with once-daily OROS MPH or atomoxetine. Investigatorrated measures of symptoms included the ADHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(124 citation statements)
references
References 19 publications
4
120
0
Order By: Relevance
“…This parallel study by Kemner and colleagues 64 reported a significant improvement in favour of MPH when measured using the ADHD Rating Scale for hyperactivity (Table 63). Similarly, the authors reported that CGI -Improvement responder rates were significantly better for the MPH group than for the ATX group (68.6 versus 52.8%, p < 0.001).…”
Section: Er-mph Medium Dose (20-40 Mg/day) Versus Atx Low/medium Dosementioning
confidence: 84%
See 3 more Smart Citations
“…This parallel study by Kemner and colleagues 64 reported a significant improvement in favour of MPH when measured using the ADHD Rating Scale for hyperactivity (Table 63). Similarly, the authors reported that CGI -Improvement responder rates were significantly better for the MPH group than for the ATX group (68.6 versus 52.8%, p < 0.001).…”
Section: Er-mph Medium Dose (20-40 Mg/day) Versus Atx Low/medium Dosementioning
confidence: 84%
“…A cost-utility analysis (classified CIC) was conducted based on the results of two recent randomised, open-label studies comparing Concerta XL with IR-MPH 90 and ATX 99 and the MTA trial. 133 The model took the form of a decision tree with a time horizon of 1 year, and was conducted from the perspective of the UK NHS.…”
Section: Review Of the Janssen-cilag Submission Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect size at 6 weeks of 0.55 had increased in almost linear manner to 0.82 at 12 weeks (Montoya et al, 2009). Thus, some of the earlier studies cited to support superior efficacy of MPH over ATX and being only of 3-6 weeks duration may not have been long enough to show the maximal ATX efficacy (Kemner et al, 2005;Newcorn et al, 2008).…”
Section: Discussionmentioning
confidence: 99%